The Time of Anthropology Studies of Contemporary Chronopolitics - Kirtsoglou, Elisabeth; Simpson, Bob (Taylor & Francis, 2020)
The Time of Anthropology provides a series of compelling anthropological case studies that explore the different temporalities at play in the scientific discourses, governmental techniques and policy practices through which modern life is shaped. Together they constitute a novel analysis of contemporary chronopolitics. The contributions focus on state power, citizenship, and ecologies of time to reveal the scalar properties of chronopolitics as it shifts between everyday lived realities and the macro-institutional work of nation states. The collection charts important new directions for chronopolitical thinking in the future of anthropological research.